An Appraisal-Transitivity Analysis of Editorials on the Results of General Elections -2018 in Pakistan - Hafiz Muhammad Qasim; Masroor Sibtain; Muhammad Shafqat Nawaz (Journal of Research in Social Sciences, 2021)
Ideology is a semiotic system and social interaction helps in realizing it through language. It is widely acknowledged that editorials are an effective tool in the construal of ideology. They contain the interpretations of key events aiming to develop an understanding of the world in readers. This study aimed to explicate the ideologies construed in the local English newspaper editorials on the results of general elections-2018 in Pakistan. The sample editorials for the analysis of ideology in this study were taken from The Express Tribune, The Nation, Dawn, and Pakistan Today. Drawing on Systemic-Functional Linguistics (Halliday & Matthiessen, 2014), particularly on appraisal and transitivity system, it examined how the linguistic choices were made in the editorials to construe, project and normalize a particular ideology. The results revealed that The Express Tribune explicitly construed an ideology that advocates the fairness of the election and gives due credit to the voter who opted for change by rejecting the political feudalism, while The Nation spoke the rhetoric of ‘irregularities and rigging’ in the elections. The editorial of Dawn was more evaluative and suggestive and had more potential to affect the opinions of the readers. Pakistan today made certain grammatical choices to implicitly negate the rhetoric of rigging in general elections-2018 in Pakistan. The study concluded that certain ideologies are construed in and through editorial by the use of certain grammatical choice to formulate the opinions of readers about the issues and events being portrayed in the editorials. The study provides insightful implications for critical discourse analysis based on Systemic Functional Linguistics.